O impacto do custo de transporte na implantação da ferrovia em Rondonópolis e no escoamento da produção de grãos das regiões Médio Norte e Centro Sul do estado de Mato Grosso - Nahsan, Gustavo Pardo Salata (2017)
The present paper analyzes the advantages and disadvantages of the modal transportation of road and rail to the city of Rondonópolis - MT, after three years of operations at the city's rail terminal. What are the prospects achieved and the benefits to the city, region, and also to the state, as a whole. It also has the focus on the contribution that this modal brought to the grain competitiveness in the world scenario and also the impacts of a single modal installed in the State of Mato Grosso. The research for the elaboration of this work is based on the use of primary sources from interviews carried out with the official bodies accredited to grain cultivation in the State of Mato Grosso, as well as some companies associated to the transportation sector located in the city of Rondonópolis. Secondary sources were also consulted through the use of bibliographic references relevant to the subject. On this basis, the analytical and exploratory method was used to discuss the results and elaborate the final work. It can be seen that the railway modal, although in the operation stage can bring direct benefits to the state as a whole, but that its potential benefits could be maximized, not only with the maintenance of prices practiced in recent years, With an economy in the final value of transport, plus a speed that would guarantee a quality of the natural product exported by the State, grains.